2021
DOI: 10.1007/s10508-021-01982-1
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults Vastly Overestimate Both HIV Acquisition Risk and HIV Prevalence in Rural South Africa

Abstract: Perceptions of HIV acquisition risk and prevalence shape sexual behavior in sub-Saharan Africa (SSA). We used data from the Health and Aging in Africa: A Longitudinal Study of an INDEPTH Community in South Africa baseline survey. Data were collected through home-based interviews of 5059 people ≥ 40 years old. We elicited information on perceived risk of HIV acquisition and HIV prevalence among adults  ≥ 15 and ≥ 50 years old. We first describe these perceptions in key subgroups and then compared them to actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This increases the possibility of polygyny, continued HIV transmission, and late HIV detection due to a low perceived risk of transmission [ 2 ]. Similarly, older people may overestimate their risk but not seek testing services due to embarrassment, adding to their stress [ 42 44 ]. In the absence of health programs to address concerns about changes in sexual function, churches and traditional teaching mechanisms in Zambia may prove valuable in holding what are locally called “conferences” on physical, sexual, financial and spiritual wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…This increases the possibility of polygyny, continued HIV transmission, and late HIV detection due to a low perceived risk of transmission [ 2 ]. Similarly, older people may overestimate their risk but not seek testing services due to embarrassment, adding to their stress [ 42 44 ]. In the absence of health programs to address concerns about changes in sexual function, churches and traditional teaching mechanisms in Zambia may prove valuable in holding what are locally called “conferences” on physical, sexual, financial and spiritual wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…The younger among the older population, with more education years, who have been or are in a marital relationship, were found to be more aware of their HIV-positive status, possibly due to lower risk perception by the older population, as well as the fact that most awareness and educational campaigns tend to focus more on the younger population. [49][50][51] The younger population seems to have a higher perception of risk than the older population. Nyirenda et al 50 found that only 9.4% of adults aged 50 years and over had a 'highrisk' HIV perception in a study comprising both rural and urban participants in South Africa.…”
Section: Discussionmentioning
confidence: 99%